Refleksije ratova na Balkanu 1912./13. godine na držanje Muslimana u Bosni i Hercegovini - Juzbašić, Dževad (Anali Gazi Husrev-Begove biblioteke, 2001)
Apart from the territories where they took place, the Wars on the Balkans 1912-1913 would have had far reaching consequences than it could have been expected. In our parts they would primarily mean the further rift and deepening of quarrel between the Moslems and the Serbs, and to the lesser extent towards the Croats, who took a rather passive position in the events. The Balkans Wars and their results would throw the Moslems of Bosnia and Herzegovina into the arms of Austro-Hungarian Monarchy. These wars led to the strengthening of the idea of Southern Slavic unity (Yugoslavianism or Yugoslavhood), especially among the Serbs, and that would mean the increased level of aggressive behavior, particularly against the Moslems. The wars would give rise to the feeling in the Moslem population that the Ottoman Turkey was no longer relevant. For this reason, the Moslem population: opted mostly for the protection under the Austro-Hungarian leadership, showed only a few signs of enthusiasm for the idea of Southern Slavic unity (Yugoslavianism). In the sources from the period one could find more and more terms that spoke about the notions that had not been that unknown but used not so often before, such as nations, nationalities etc. In the previous period the Serbian side emphasized the struggle for the Cross and Honor, and the Moslem one the struggle for the Faith and Empire (din and devlet). For the first time one could hear the notion uttered about one nation, only with three names and religions. In this period people were asked to declare their ethnic affiliation although this issue was more popular and less real. One could conclude that the Bosnian-Herzegovinian Moslems had taken very little part in the Balkans Wars (having sent only a small number of volunteers), but they felt much more the consequences and results of these wars.